Efektivitas Penginjilan Pribadi dan Penginjilan Massal dalam Konteks Jangkauan Misi - Banjarnahor, Delima; Gultom, Rogate Artaida Tiarasi; Damanik, Dapot (Jurnal Apokalupsis, 2025)
This study is motivated by the issue of the effectiveness of personal and mass evangelism in reaching a society that is increasingly complex in its social, cultural, and technological dimensions. The purpose of this research is to analyze the effectiveness of both approaches and to identify synergistic strategies that can enhance the church’s mission outreach in a sustainable and contextual manner. The research employs a qualitative descriptive method with a literature-based approach, analyzing various theological and missiological sources. The thesis of this study asserts that personal and mass evangelism each have their own strengths and weaknesses, yet they can complement one another when integrated within a contextual mission framework. The findings indicate that the integration of these two methods can both expand the reach of the mission and deepen discipleship through relational engagement and the use of technology. The conclusion emphasizes that cross-institutional collaboration, evangelist training, and the development of contextual theology are key to an effective and relevant church mission strategy in the modern era. The study recommends that churches develop an integrative mission model that adapts to social dynamics and digital advancements so that the Great Commission of Christ can be realized effectively and sustainably